Loyalty of Employee and Loyalty of Client on the Example of Enterprises of Multi-level Marketing (MLM) - Warzecha, Alina (Edukacja Ekonomistów i Menedżerów, 2012)
In modern business conditions talented and effective workers who well know specificity of enterprise and their competition become – after their clients – the most valuable assets. The modern enterprises must build both loyalty of client and the workers’ loyalty. This article presents the definition of loyalty used by marketing specialists and shows the dependences of loyalty of clients and loyalty of staff using the model of sector of MLM enterprises.